INTOLERANCE OF UNCERTAINTY AS A MEDIATOR OF THE RELATIONSHIP BETWEEN PERFECTIONISM AND OBSESSIVE‐COMPULSIVE SYMPTOM SEVERITY. Issue 8 (22nd April 2013) - Reuther, Erin T.; Davis, Thompson E.; Rudy, Brittany M.; Jenkins, Whitney S.; Whiting, Sara E.; May, Anna C.
<x xml:space="preserve">Abstract</x> Background Intolerance of uncertainty (IU) and perfectionism have both been shown to predict severity of obsessive–compulsive disorder (OCD) symptoms in populations diagnosed with OCD, as well as analogue samples. According to cognitive models of OCD, symptoms are maintained by dysfunctional beliefs including IU and perfectionism. The purpose of the current study is to extend research on the cognitive theory of OCD by describing how dysfunctional thoughts interact with each other. Methods In an analogue sample for OCD (N = 475), undergraduate students completed measures online pertaining to IU (IU scale), perfectionism (Frost Multidimensional Perfectionism Scale), and OCD symptoms and severity (Florida Obsessive–Compulsive Inventory). Results The proposed model of IU fully mediating the relationship between perfectionism and OCD severity was supported using structural equation modeling (SEM) analysis. Bootstrapping testing within AMOS 20 and Sobel tests further corroborated full mediation. Conclusions Results from the current study suggest that IU fully mediates the relationship between perfectionism and severity of OCD symptoms. This finding has an impact for understanding the nature and treatment of OCD with perfectionism as a primary symptom. Findings suggest that in order to address perfectionism, it is necessary to first treat cognitions and obsessions associated with IU and that this practice would lessen distress and interference associated with perfectionistic obsessions.